If x = 1 is a common root of ax² + ax + 2 = 0 and x² + x + b = 0 then, ab =
A. 1
B. 2
C. 4
D. 3
Answers
Answered by
0
Answer:
b is the correct option
Answered by
0
B. 2
Step-by-step explanation:
x = 1 is a common root of ax² + ax + 2 = 0 and x² + x + b = 0
Substituting x = 1 in ax² + ax + 2 = 0, we get:
a + a + 2 = 0
2a = -2
a = -1 -----(1)
Substituting x = 1 in x² + x + b = 0, we get:
1 + 1 + b = 0
b = -2 -----(1)
Now from 1 and 2, we get ab = -1 * -2 = +2
Option B is the answer.
Similar questions